Heterochromatin patterns in four diploid Zephyranthes species with different basic chromosome number (Amaryllidaceae) - Gianini Aquino, Analía Cecilia (2023)
Diverse species-specific karyotypes have been reported within Zephyranthes Herb., as well as different basic chromosome numbers (x = 5, 6, 7, and 9), with x = 6 being the most common. The aim of this work was to analyze the constitutive heterochromatin (C-Het) pattern of karyotypes in four diploid Zephyranthes species. For this purpose, a cytomolecular analysis of the karyotypes of Z. andalgalensis (2n = 2x = 12 = 4 m + 2 sm), Z. chacoensis (2n = 2x = 12 = 3 m + 2 sm + 1 st), Z. robusta (2n = 2x = 12 = 3 m + 2 sm + 1 st), and Z. pedunculosa (2n = 2x = 14 = 1 m + 3 sm + 3 st) was performed for the first time. All the species analyzed showed CMA+ terminal bands that could be distinguished by their heterochromatin pattern. Interestingly, DAPI+ interstitial bands were also found in the karyotype of Z. robusta. The four Zephyranthes C-Het patterns analyzed show that diploid species have little GC-rich heterochromatin, which is generally associated with terminal satellites, and that AT-rich heterochromatin is rare. The dysploidy evolutionary change between two basic chromosome numbers (x = 6 and 7) is discussed in the present study.